2017
DOI: 10.20302/nc.2017.26.14
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling food webs interactions in the littoral of temperate shallow lakes

Abstract: Elucidation of food web interactions provides a better understanding of ecosystem functioning, indicates anthropogenic impacts which often cause alterations in environmental conditions and deterioration in feeding networks in terrestrial and aquatic ecosystems. The importance of microfauna and macroinvertebrates in the littoral zones of shallow waters has been poorly studied regarding their trophic interactions. This study compares invertebrate assemblage and food web interactions among epiphyton, zooplankton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Predation by rotifers in freshwaters has important effects on prey communities including their species composition, nutrient cycling, and trophic dynamics (e.g., Edmondson, 1946; Gilbert, 1980; Miracle et al, 2007; Nandini & Sarma, 2005; Špoljar et al, 2017; Yoshida et al, 2003). While prey selectivity has been studied in several free‐swimming, raptorial species (Ardnt, 1993; Gilbert, 1977; Nandini et al, 2003; Nandini & Sarma, 2005; Williamson, 1983), little is known about the feeding of raptorial sessile species.…”
Section: Introductionmentioning
confidence: 99%
“…Predation by rotifers in freshwaters has important effects on prey communities including their species composition, nutrient cycling, and trophic dynamics (e.g., Edmondson, 1946; Gilbert, 1980; Miracle et al, 2007; Nandini & Sarma, 2005; Špoljar et al, 2017; Yoshida et al, 2003). While prey selectivity has been studied in several free‐swimming, raptorial species (Ardnt, 1993; Gilbert, 1977; Nandini et al, 2003; Nandini & Sarma, 2005; Williamson, 1983), little is known about the feeding of raptorial sessile species.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, water mites (35%) prevailed among the hornwort (Ceratophyllum) coverage in Cro1, adult hemipterans (23%) overcome in Cro2, and in Cro5 dipteran larvae constituted a considerable share (51%) in the littoral ecotone zone, with very sparsely developed emergent macrophytes or their absence. Moreover, very important is possibility of refuge against predators in the sediment, due to results indicated an increased presence of buried planktonic crustaceans in the conditions of the increased abundance of macroinvertebrate predators, mainly dipteran and dragonfly larvae in the littoral zone [24,25]. Food web modelling indicated zooplankton and epiphyton as crucial food subsidies for invertebrate predators among complex submerged macrophyte than among the floating-leaved macrophyte stands (Fig.…”
Section: Macroinvertebrates Interplays In the Littoral Zone Of Shallow Water Ecosystemsmentioning
confidence: 97%
“…Submerged macrophytes in the littoral zone enable the shelter to the largesized zooplankters against fish during the day. For many zooplankters littoral zone with macrophytes is not an adequate surviving solution, because there encounter macroinvertebrate, such as tactile predators [24,25]. Also, many studies suggested the existence of different alternative states at the same trophic conditions, where the absence of macrophyte coverage and presence of cyprinids could cause a shift into a turbid state [22,25].…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Dinoflagella are known because of their whip-like frills. Some of them live by photosynthesis, and some other types of plankton eat others [3] and some are able to produce light. Some of the plankton and fish parasites and others are able to secrete a toxic substance [4].…”
Section: Introductionmentioning
confidence: 99%